Analytical Method Development and Validation of Simultaneous Estimation of Pure and Tablet Dosage Form by RP-HPLC - Thapa, Shankar; Pandey, Bipindra Pandey; Biradar, Mahalakshami Suresha (Journal of Nepal Chemical Society, 2024)
The aim of this analytical research is to establish and validate the RP-HPLC (Reverse Phase High Performance Liquid Chromatography) method for concurrently quantifying Montelukast Sodium, Fexofenadine Hydrochloride, and Acebrophylline in a pharmaceutical formulation. The method utilized Rosagiline mesylate as an internal standard, employing a Shim-Pack Solar C18 Column (4.6 x 150 mm, 5 µm) as the stationary phase and a mobile phase composed of acetonitrile, methanol, and 10 mM Na2HPO4 buffer (50:30:20 % v/v/v, pH 5.5). The flow rate was maintained at 1.0 mL/min, and detection occurred at 210 nm. Validation followed ICH guidelines. The linear concentration ranges were 5-30 µg/ml, 10-60 µg/ml, and 10-100 µg/ml at 210 nm for Montelukast Sodium, Fexofenadine Hydrochloride, and Acebrophylline, respectively. Retention times were 7.643 min, 2.117 min, 3.863 min, and 3.050 min for Montelukast sodium, Fexofenadine Hydrochloride, Acebrophylline, and Rosagiline mesylate respectively. The RP-HPLC analysis of marketed formulations yielded concentrations within the ranges of 98.3–100.9%, 99.46–101.23%, and 99.82–101.74% for Montelukast sodium, Fexofenadine Hydrochloride, and Acebrophylline, respectively. Recovery fell within the range of 95.81-101.35% for both drugs. The proposed method has been validated as per ICH guidelines and successfully applied to the estimation of Montelukast, Fexofenadine and Acebrophylline in their combined tablet dosage form.